Digitalisation and intelligent robotics in value chain of circular economy oriented waste management – A review - Sarc, R.; Curtis, A.; Kandlbauer, L.; Khodier, K.; Lorber, K.E.; Pomberger, R. (Waste management (Elmsford), 2019)
•Digitalisation & intelligent robotics are tools in value chain of waste management.•Municipal waste management development is defined by Circular Economy Package.•4 segments: Collection & Logistics, Machines & WTP, Business Models and Data Tools.•Extensive survey of (inter)national data (period 2001–2019): 114 sources utilized.•Smart Waste Factory: Machines are digitally connected and communicate with waste. The general aim of circular economy is the most efficient and comprehensive use of resources. In order to achieve this goal, new approaches of Industry 4.0 are being developed and implemented in the field of waste management. The innovative K-project: Recycling and Recovery of Waste 4.0 - “ReWaste4.0” deals with topics such as digitalisation and the use of robotic technologies in waste management. Here, a summary of the already published results in these areas, which were divided into the four focused topics, is given: Collection and Logistics, Machines and waste treatment plants, Business models and Data Tools. Presented are systems and methods already used in waste management, as well as technologies that have already been successfully applied in other industrial sectors and will also be relevant in the waste management sector for the future. The focus is set on systems that could be used in waste treatment plants or machines in the future in order to make treatment of waste more efficient. In particular, systems which carry out the sorting of (mixed) waste via robotic technologies are of interest. Furthermore “smart bins” with sensors for material detection or level measurement, methods for digital image analysis and new business models have already been developed. The technologies are often based on large amounts of data that can contribute to increase the efficiency within plants. In addition, the results of an online market survey of companies from the waste management industry on the subject of waste management 4.0 or “digital readiness” are summarized.